2021
DOI: 10.1002/pits.22567
|View full text |Cite
|
Sign up to set email alerts
|

The effects of teacher–child racial congruence, child race, and emotion situation knowledge on teacher–child relationships and school readiness

Abstract: We examined whether teacher–child racial congruence and child race moderated the association between children's emotion situation knowledge and the dimensions of teacher–child relationship quality (i.e., closeness, conflict, and dependency). We also investigated these dimensions as mediators linking emotion situation knowledge and later school readiness. Participants were 303 White and African American preschoolers and their teachers who were also racially diverse. For White preschoolers, teacher–child closene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 136 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…Some other studies have explored the role of children's emotion understanding in nurturing teacher-child relationships. Garner and Mahatmya (2015) and Garner et al (2021) consistently showed that high levels of emotion knowledge were related to teacher-child closeness in 4-year-olds, and this association was moderated by the children's and the teachers' races. It is noteworthy that prior work has mostly tested the unidirectional effect either from teacher-child relationships to emotion understanding or from emotion understanding to teacher-child relationships.…”
Section: Teacher-child Relationship Qualitymentioning
confidence: 89%
“…Some other studies have explored the role of children's emotion understanding in nurturing teacher-child relationships. Garner and Mahatmya (2015) and Garner et al (2021) consistently showed that high levels of emotion knowledge were related to teacher-child closeness in 4-year-olds, and this association was moderated by the children's and the teachers' races. It is noteworthy that prior work has mostly tested the unidirectional effect either from teacher-child relationships to emotion understanding or from emotion understanding to teacher-child relationships.…”
Section: Teacher-child Relationship Qualitymentioning
confidence: 89%
“…Ecological incongruence between home and school contexts can heighten the chances for misunderstandings between teachers and students regarding emotions, behaviors, and perspectives (e.g., Garner et al, 2021; Halberstadt et al, 2022). These discrepancies could potentially exacerbate relational challenges between teachers and students in ways that are distinct from mere teacher bias.…”
Section: Introductionmentioning
confidence: 99%